(untitled) (Studia Doctoralia Psychology and Educational Science, 2025)
In an evolving world where artificial intelligence increasingly reshapes our daily lives, and people are starting to talk more often to algorithms, one question inevitably emerges: is it safe and ethical to use AI for mental health care? Let’s talk about that.